Association of environmental exposure to heavy met-als with chronic kidney disease (CKD) in patients from White Nile province, Sudan - M.E, Elzin; E .H, Mohamed; M I, Abdelgadir (International Journal of Health, 2023)
This research was focused on assessment of chronic kidney disease (CKD), due to the contamination of water, in White Nile Province, Sudan with heavy metals, agrochemicals, hard water, ionicity, and climate changes. Nevertheless, the levels of any of the pollutants or conditions reported in this water are inconsistent not correlated with the prevalence of the disease and are too low to cause (CKD). The most common cause of chronic kidney disease (CKD) among all groups was diabetes mellitus (46.50%); followed by hypertension (46.50%); chronic glomerulonephritis (7.64), while other causes account for only (9.55%). The highest prevalence of CKD was recorded in Eld – Duiem, followed by Allahamed localities, with a percentage of (22.9% and 17.8%), respectively. The highest prevalence of the cases was recorded in patients of the range age of 31-50 years, followed by patients from the group 51-70 years old, and least in the group of 71-90 years old. Famers recorded a frequency of (20.38%) and sponsors recorded a frequency of (17.20%), while, among groups of other occupation a high frequency of (42%) was recorded. The level of education reflected a high frequency of CKD among the individuals of primary education, followed by individuals of secondary education, while the lowest frequency was recorded among illiterates. People living in red brick building, recorded the highest number of CKD patients (142 patients) while only (5 patients) who live in wool building were recorded. On the other hand, high prevalence of CKD (113 patients) was recorded in groups who do not take herbs, while the more patients (44) were recorded among individuals who take herbs. All results showed significance of (P ≤ 0. 05).